Kaji Eksperimental Torsi Statik Dan Dinamik Turbin Hidrokinetik Savonius Type Bach Tiga Sudu Menggunakan Plat Pengarah - T. Budi Utomo Syafri; Iwan Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Installation of the directional blade in the front of the rotor can improve the performance of the savonius turbine, because it can prevent negative torque on the convex side of the rotor and direct the amount of water mass on the concave side of the rotor without affecting the convex side of the rotor. This study aims to find the dynamic torque and static torque of the savonius type bach hydrokinetic turbine using the streering plate with variation α 30˚:β 10˚, α 45˚:β 10˚, and α 60˚:β 10˚ utilizes water as the driving fluid with variations in the velocity of water flow 0.34 ⁄ and 0.51 ⁄ and is carried out using experimental methods on a laboratory scale. Based on the tests carried out, at a water flow rate of 0.34 ⁄ the maximum dynamic torque of 0.48 Nm was obtained at angle variation α 45˚:β 10˚, while at a speed of 0.51 ⁄ water flow obtained dynamic torque maximum of 0.60 Nm in angle variation α 45:β 10˚. Maximum static torque is 0.66 Nm in angle variation α 45˚:β 10˚.Keywords: Savonius hydrokinetic turbine, guide blade, dynamic torque, static torque